A semiose da escrita e sua reconfiguração na hipermídia: uma análise semiótico-sistêmica - Jungk, Isabel Victoria Galleguillos (2011)
With the advent of Internet and hypermedia technologies for text transmission, new spellings of words of the lexicon are becoming common as a form of adaptation of written language to digital media and its peculiarities. The main target of the present research is to investigate the manifestations and potentials of the written word in these new spelling characterized by a considerable degree of hybridism and complexity. The starting point is the assumption that the semiotic analysis of the word within the language system and of the written word reconfigured in hypermedia, given its eminently hybrid features, can be facilitated by using the classification of signs devised by Charles S. Peirce and by the distinction drawn between the word as a general law and its effective application. Aiming to examine the theoretical context in which changes have occurred, a systemic approach to the writing system as well as to hypermedia is adopted, according to the general systems theory as developed by Jorge A. Vieira. Questions concerning the challenges posed by this new kind of writing to conventional writing are raised through specialized bibliography on verbal language at hypermedia, auxiliary of the problem contextualization. The corpus consists of practical examples of the transmutations of the semiotic nature of writing and of new spellings. Corpus analysis is done by means of semiotic concepts appropriately operationalized to the needs required by the research object. It is expected that the research results will lead to a critically founded understanding of evolutionary processes of writing